Răspunsuri

Cel mai inteligent răspuns!
2014-05-09T22:33:33+03:00
F(- 2011/2 )= 2* (-2011/2)+1= -2011+1= -2010
f(-2009/2) =2*(-2009/2)+1= -2009+1= -2008
f(-2007/2)= 2*(-2007/2)+1= -2007+1=-2006
............................................................................
f(2011/2)=2*(2011/2)+1=2011+1=2012
f(2013/2)= 2*(2013/2)+1=2013+1=2014

S=(-2010)+(-2008)+(-2006)+........+(2012)+(2014)
2[(-1005)+(-1004)+(-1003)+..........+(1006)+(1007)

S=2[(-1005)+(1007)]*2012/2
S=(-1005+1007)*2012
S=2*2012
S=4048
1 5 1